Asymmetric syntheses of (- )-hastanecine, (- )-turneforcidine and (- )-platynecine - Davies, S; Brambilla, M; Fletcher, A; Roberts, P; Thomson, J (Elsevier, 2016)
Concise total asymmetric syntheses of three diastereoisomeric 1-hydroxymethyl-7-hydroxy substituted pyrrolizidines, (−)-hastanecine, (−)-turneforcidine and (−)-platynecine, are reported. The doubly diastereoselective conjugate additions of lithium (R)- or (S)-N-benzyl-N-(α-methylbenzyl)amide to tert-butyl (R,E)-4-(triethylsilyloxy)hepta-2,6-dienoate [which was prepared (in 96:4 e.r.) via Lewis acid mediated catalytic asymmetric allylation of tert-butyl (E)-4-oxobut-2-enoate] proceeded in both cases under the dominant control of the lithium amide reagent. Subsequent diastereoselective enolate allylations installed the required stereogenic centres, and the pyrrolizidine ring system was rapidly accessed by a two-step protocol (viz. ozonolysis and one-pot hydrogenolysis/double reductive cyclisation), to complete the asymmetric syntheses of (−)-hastanecine, (−)-turneforcidine and (−)-platynecine in 17, 8 and 24% overall yield, respectively, in eleven steps from commercially available 2,2-dimethoxyacetaldehyde in each case.